Essential oil as a new tool for larvicidal Aedes aegypti: A systematic review - Budiman; Hasanuddin Ishak; Stang; Erniwati Ibrahim; Anwar Daud; Ridwan Amiruddin (Elsevier, 2021)
Objective: The study aimed to describe the effectiveness of essential oil plants for Aedes aegypti mosquito vector control. Methods: This systematic review selection process following with 2015 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guideline. The source of the articles from databases international journal were Scopus, Pubmed, Scinapse and Google Scholar. Result: Natural control management with essential oil is the way of alternative for larvicidal mosquito control especially A. aegypti. The essential oil for many plants can use for larvicidal against A. aegypti as Piper batle L., Tinospora rhumpii, Azadiractha indica, Persea americana, Piper aduncum, Leucas aspera, Eucaliptus camaldulensis, Ottonia anisum, Salvia Plebeian, Lantana camara, and Syzygium aromaticum with 100% mortality larvae A. aegypti at 48 h. Conclusions: The vector borne diseases must be used to integrate vector management control with essential oils plants.